Development of Social institution of Mass media in Information Society and Legal Field of the Personal and Corporative Information Security - Alexander Anatolyevich Markov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The crucial role of information in the post-industrial society leads to the necessity and actuality of social sciences’ studying mass communication channels. Sociological analysis of mechanisms and tools of the information and knowledge’ creation and transmission, as well as channels of open access to data and competences, raises questions on the new opportunities, but also on the social constraints for the functioning of mass communication systems. As part of this perspective, the proposed material focuses on the problems of the evolution and dynamics of security issues from the point of view of social-legal assessment of the functioning of the Institute of Mass Communication in the Information Society. The submission is built in the inferential deductive logic, from the general analysis of the information society and the studies of institutionalizing communicative channels and regulatory mechanisms that establish restrictions, crucial for individual and community’ protection, towards the implementation of the private information security of individuals and corporate actors. Analysis of regulators of the behavior in the postmodern socio-cultural environment at the level of micro-sociological empirical research is carried out in terms of legal protection of honor and dignity of individuals and of corporate identity. The theoretical and practical analysis concludes on the need to formalize and differentiation of types of legal regulatory models. By identifying the specific features of the information society, revealing the elements of the traditional society, the study concerns the dynamics of the role of information as a resource and as a form of existence of the actor in the space of an information society. In view of the interpretation of information security as a society’s ability to minimize the obstacles to the free realization and actualization of socially acceptable interests of individuals and groups, the material deals with a theoretical question of protection of data, and with theoretical and practical sociological and legal purposes of the protection against abuse and violation of the integrity and credibility.